THE DA’WA STRATEGY OF @NGAJIASIK.ID COMMUNITY - Rahmah, Safira Aulia; Zulhazmi, Abraham Zakky (QAULAN: Journal of Islamic Communication, 2022)
Abstract: In the era of advanced technology today, there are many ways to preach. One way used when today is forming a migration community. Hijrah Community @ngajiasik.id. This community carries the concept of young people, with a student who is cool and principled that the recitation is fun. Strategies can be interpreted as a method of gathering information and organizing, so that it can estimate a hypothesis. The method used for this study is a qualitative research method, using observation methods and interviews as a method of data collection in this study. The Hijrah @ ngajiasik.id community plays a role in moving the community to provide a means of improving the quality of public faith and spreading Islamic da'wah widely. The strategy used in preaching is to use a contemporary da'wah strategy. The strategy used in the dissemination of da'wah is the determination of the objectives of the da'wah, preparation of the implementation of the strategy, the preparation of plans, and the process of implementing the strategy.